E-Module Development using the Four-D Model in Computer Systems Subjects for 10th Grade of Computer and Network Engineering Expertise Program at SMKN 3 Malang - Vearen Dika Sofirudin; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Journal of Information Technology and Computer Science, 2022)
This research aims to explain the results of needs analysis in development e-module using the four-d model in computer systems subjects and explains the results of measuring the success rate of implementing e-modules using the four-d model in computer systems subjects. E-Module is a type of digital learning media that is arranged systematically and attractively by utilizing electronic devices. The method used is research and development or the R&D four-d model. The model research four-d consists of four stages of development, including (1) definition, (2) design, (3) development, and (4) dissemination. The subjects of this study were students of 10th grade majoring in 1st Computer and Network Engineering at Vocational High School 3 Malang, while the research instruments used were validation e-module sheets, pre-test and post-test question sheets, assessment sheets, and student response questionnaires. Based on the results of the study, it was found that: (1) In developing e-module products, researchers have adjusted to the characteristics of students who find it difficult to understand theoretical material, especially in computer systems subjects. So that the presentation of content e-module is in the form of text, images, and videos to make it easier for students to learn the material independently. (2) The results of measuring the success rate of application e-module through the Paired Sample T-Test by comparing the pre-test and post-test results, namely a significance value of 0.000. The acquisition of a significance value that is less than 0.05 means that there are differences in learning outcomes before and after using the e-module.Keywords. development, e-module, computer systems, Four-D models